"Food is something everyone should participate in": A positive deviance approach to understanding the use of a food and nutrition app in low-income, Latino homes. (June 2020) - Neffa-Creech, Deborah; Clarke, Peter; Evans, Susan H; Glovinsky, Joanna
Objectives: Latino families are among the most likely to be overweight or obese, which are conditions associated with numerous health risks and diseases. These families might lack know-how for preparing vegetables that fall outside cooks' culinary comfort zones and cultural traditions. Mobile apps are increasingly being developed for healthier cooking and eating, but research has not much explored how such apps are used among these families to help facilitate changes in eating patterns. This research seeks to identify behaviors and motivations that lead household cooks (i.e. mothers) in low-income Latino homes to use a food and nutrition app and create healthier eating environments for their families. Methods: This study uses a positive deviance approach and individual interviews with mothers who were frequent app users and experienced beneficial food outcomes during their participation in a randomized controlled trial that tested the effects of an app on their cooking and family eating behaviors. Interviews were analyzed for themes using a framework analysis approach. Results: Three themes emerged across interviews that were suggestive of approaches that led mothers to become frequent app users and prepare healthier meals: (1) mothers invited their children to use the app; (2) they involved both sons and daughters in the kitchen; and (3) they (cautiously) stepped outside their culinary comfort zones. Conclusion: Mobile apps and app-focused interventions should include features that invite: app co-use between mothers and children; opportunities for mothers to socialize boys, as well as girls into kitchen routines; and the use of culturally-familiar ingredients or recipes that are easily adaptable.